External Conflicts Found in Kenneth Grahame's "The Wind in the Willows" Novel - I Gusti, Ayu Wiryastini; Ida, Ayu Mela Tustiawati (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2024)
Literature provides distinctive perspectives on human’s behaviour, prompting us in creative thinking and igniting fresh ideas as well as discussions. Novel, as one of the literature forms, needs creative ideas to create one. Conflict has a crucial part in novel, which to move the plot forward. This study aims to discover the conflicts that happens in the novel faced by the main characters and how the characters resolve it. Kenneth Grahame’s novel The Wind in the Willows is used as the data of this study. The types of conflict theory proposed by Kenney (1996) is employed to analyse the data. The techniques used to collect the data were observation method and note-taking. The observation method means the researcher had read the novel accurately whereas the note-taking method used to mark and point out the types of conflict occurred in the novel. As the result, the researcher discovered that there are two types of conflict occurs in the novel, internal and external conflict with the external conflict takes the dominant conflict that occurs more frequently. The external conflict mainly happens between the main characters and against the nature, whilst the internal conflict happens between the characters against their inner turmoil and feelings.